Do the standards need modifications? A proposal for geotechnical stability safety factor of breakwater. Issue 1 (April 2021) - Mollaert, J; Tavallali, A; Maertens, J
Abstract: In different countries and continent, different standards are followed for geotechnical stability safety factors of breakwaters which are not exactly in the same line. Parties involved in breakwater design and construction projects might follow different procedures/standards (load cases to be analysed and the acceptable safety factor). It is a fact that a clear table that shows the acceptable safety factors for different load cases is not clearly presented in the standards. So the aim is to provide a proposal that covers all the standards. In this paper, four guidelines/standards of "Rock Manual", "US Army Corps of Engineers", "Eurocodes" and "ROM" are reviewed. Based on the mentioned standards and some considerations a table that shows the acceptable safety factors for different load cases is presented. Another concerns is that the actual more powerful and advanced calculation software allows to find the results with less uncertainty compared to the formerly applied methods. It means that lower safety factors in comparison to the old methods can be applied and accepted with the recent software. The aim of the paper is presenting a procedure for the slope stability safety factors in order to reduce the amount of discussions and disagreements that of course come from the interpretations of different standards. Furthermore, reduced slope stability safety factors for different load cases are proposed.